Staphylococcus aureus nasal carriage in medical students of Universiti Teknologi MARA / Zaini Mohd Zain ... [et al.] - Mohd Zain, Zaini; Johari, Muhammad Fikri; Mohd Husin, Nurul Shahirah; Rozman, Nurul Syamimi; Ab Rashid, Athirah; Bahanuddin, Latifah; Mohamad Zain, Muhammad Ilyas Danial (Universiti Teknologi MARA Cawangan Selangor, 2017)
To determine the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) nasal carriage and detection of S. aureus leukotoxins among medical students of Universiti Teknologi MARA. Methods: Both sides of the anterior nares of 136 volunteers, comprising 68 preclinical and 68 clinical medical students, were swabbed and immediately cultured onto mannitol salt agar for growth of S. aureus. Standard microbiological techniques were conducted to identify and confirm the S. aureus colonies and susceptibility test against oxacillin were conducted by using Kirby-Bauer method to determine their resistance to methicillin. Polymerase chain reaction was performed for detection of leukotoxins, i.e., Panton-Valentine Leukocidin (PVL) and -haemolysin genes. Results: Nineteen students (14%) consisting of 10 preclinical (14.7%) and 9 clinical (13.2%) were nasal carriers of S. aureus. However, none of the S. aureus isolates were MRSA. No PVL gene was detected but eight of them were positive for -haemolysin gene. Conclusion: There were no MRSA nasal carriers among the medical students, but a low prevalence of S. aureus nasal carriers was detected. These carriers do not pose as high risk because none of the strains of S. aureus possess both the -haemolysin toxin and the PVL toxin that are associated with tissue necrosis.